2010
DOI: 10.4049/jimmunol.0902765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyclonal IgG Derived from Patients with Different Clinical Types of the Antiphospholipid Syndrome on Monocyte Signaling Pathways

Abstract: A major mechanism of hypercoagulability in the antiphospholipid syndrome (APS) is antiphospholipid antibody (aPL)-mediated up-regulation of tissue factor (TF) on monocytes via activation of toll-like receptors (TLR), p38 mitogen activated protein kinase (MAPK) and nuclear factor (NF) κB pathways. We examined whether monocyte signalling pathways are differentially activated by IgG from patients with vascular thrombosis (VT) alone compared with IgG from patients with pregnancy morbidity (PM) alone. We purified I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 39 publications
(53 reference statements)
2
69
2
Order By: Relevance
“…We purified immunoglobulin G (IgG) from patients with APS who had VT but no PM (VT 1 /PM 2 ) or PM but no thrombosis (VT 2 /PM 1 ). We found that only VT 1 /PM 2 IgG activated NF-kB, p38MAPK, and upregulated TF activity in monocytes 5 despite there being no significant differences in aPL binding between the VT 1 /PM 2 and VT 2 /PM 1 samples.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We purified immunoglobulin G (IgG) from patients with APS who had VT but no PM (VT 1 /PM 2 ) or PM but no thrombosis (VT 2 /PM 1 ). We found that only VT 1 /PM 2 IgG activated NF-kB, p38MAPK, and upregulated TF activity in monocytes 5 despite there being no significant differences in aPL binding between the VT 1 /PM 2 and VT 2 /PM 1 samples.…”
Section: Introductionmentioning
confidence: 78%
“…1 This aPL-b 2 GPI interaction in the presence of a second stimulus leads to cellular activation and upregulation of proinflammatory/coagulant factors on target cells, 2 such as tissue factor (TF) on monocytes. [3][4][5] Current tests used to identify aPL in patients with the APS are anticardiolipin (aCL) and/or anti-b 2 GPI and/or lupus anticoagulant (LA) assays. 6 Positive results, however, in these assays often fail to predict clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups showed that TLR2 but not TLR4 is involved in aPL-mediated cell activation (Satta et al, 2007(Satta et al, , 2011Alard et al, 2010), and a single group report has been published on the direct binding of b2GPI to TLR2 (Alard et al, 2010). By contrast, two groups reported that siRNA-mediated inhibition of TLR2 expression on ECs or anti-TLR2 blocking antibody pretreated monocytes did not affect the aPL-induced pro-coagulation state, suggesting that TLR2 may play a limited role in the activation of unperturbed cells (Lambrianides et al, 2010;Allen et al, 2012). The reasons for these large discrepancies between laboratories are not known.…”
Section: Open Questionsmentioning
confidence: 97%
“…Analysis of the fine epitope specificity of b2GPI-dependent aPL is still a limitation in most studies. Most of the experiments involving TLR4 used total IgG or IgM samples isolated from serum or plasma of APS patients containing a variety of different antibodies Mulla et al, 2009;Lambrianides et al, 2010), some studies used affinity-purified anti-b2GPI IgG rather than total IgG Sorice et al, 2007), and others used animal antibodies (Zhou et al, , 2012Allen et al, 2012). It is striking that these polyclonal IgG samples were obtained from very small numbers of individual patients.…”
Section: Open Questionsmentioning
confidence: 99%
“…However, we still believe that obstetric APS does represent a distinct biological entity in comparison with the vascular variant. For example, β 2 -GPI is present only on the endothelial cells of uterine vessels but not on other vascular districts in resting animals; and aPL-positive IgG fractions from pure obstetric patients trigger different cell signaling in comparison with those from thrombotic APS sera 15,16 .…”
Section: Rheumatologymentioning
confidence: 99%